Ethnographic Research in Gendered Organizations: The Case of the Westminster Parliament. Issue 4 (9th December 2014) - Crewe, Emma
Abstract : Anthropologists and new institutionalist scholars studying politics share an interest in rules, norms, and power. The former tend to agree more closely with those researchers who rely on inductive empiricism rather than deductive research methods, take an historical perspective, and treat ambiguities as part of the study rather than an inconvenience. As Olivier de Sardan argues, those institutionalist approaches that tend to rely on abstract, predetermined structures contrast with the way anthropologists see social norms as emerging out of interaction between people in specific contexts (2014, 288).